Economic Efficiency Versus Legal Dogmatics: A Critical Analysis of Restorative Justice for Indonesian Petty Corruption - Nasrullah Arsyad; Satrih Hasyim (UIN Sunan Gunung Djati, 2026)
The normalization of petty corruption in Indonesia poses a significant sociological and institutional challenge, as evidenced by high rates of public participation in gratification. Paradoxically, law enforcement officials frequently respond to this phenomenon through a pragmatic discourse advocating restorative justice to achieve budgetary efficiency. This research aims to critically evaluate this cost efficiency argument by analyzing the normative and sociological implications of resolving corruption offenses through non-penal mechanisms. Utilizing a normative legal research methodology encompassing statutory, conceptual, and case approaches, this study examines the tension between empirical case handling expenditures and foundational rule of law principles. The findings reveal that the substantial disparity between enforcement expenditures and recovered state assets does not provide a sufficient legal basis to justify the decriminalization of corruption. Law enforcement costs represent a core constitutional function that cannot be reduced to a profit oriented calculation. Sociologically, implementing peaceful resolution mechanisms within a high tolerance society creates a significant risk of institutionalizing impunity and may encourage the collective imitation of corrupt behavior. Furthermore, a dogmatic reconstruction affirms that Article 4 of Law Number 31 of 1999 and Article 82 letter c of Law Number 20 of 2025 explicitly exclude corruption offenses from extrajudicial resolutions, as the inherent mens rea element cannot be nullified by mere asset restitution. Consequently, this research concludes that addressing this challenge requires prioritizing a summary proceedings mechanism alongside the modernization of digital prevention systems. This integrated approach ensures legal certainty, maintains the deterrent effect of criminal law, and safeguards institutional integrity without compromising procedural efficiency.